2007
DOI: 10.1021/pr060489g
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Serum from Type 2 Diabetics with Nephropathy

Abstract: Diabetic nephropathy (DN) is a renal disease which develops as a consequence of diabetes mellitus. Microalbuminuria is the earliest clinical sign of DN. There are no specific diagnostic biomarkers for type 2 diabetics with nephropathy other than microalbuminuria and macroalbuminuria. However, microalbuminuria does not constitute a sole independent indicator for type 2 diabetics with nephropathy, and thus, another screening method, such as a biomarker assay, is required in order to diagnose it more correctly. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 51 publications
1
59
0
Order By: Relevance
“…Differential proteome expressions among the non-diabetic and STZ-induced groups at six and 24 weeks were analyzed by 2-DE and nano-LC-ESI-MS/MS. Among these identified proteins, we focused on Gpx3 and annexin A3 because a literature survey [25,26] suggested their potential as biomarkers for diagnosing DN, as well as the availability of readily available reagents such as antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Differential proteome expressions among the non-diabetic and STZ-induced groups at six and 24 weeks were analyzed by 2-DE and nano-LC-ESI-MS/MS. Among these identified proteins, we focused on Gpx3 and annexin A3 because a literature survey [25,26] suggested their potential as biomarkers for diagnosing DN, as well as the availability of readily available reagents such as antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that subjects with type 1 diabetic nephropathy had an increased ApoE level (26). Another study used twodimensional electrophoresis to identify serum biomarkers for the diagnosis type 2 diabetic nephropathy and found that ApoE was a potential biomarker (27). The present study was the first large sample association study of lipids levels with type 2 diabetic nephropathy in Chinese, which included ApoE as one of the lipid metabolism parameters.…”
Section: Discussionmentioning
confidence: 71%
“…Rac1/Cdc42 antibody with sequence similarities that recognized endogenous levels of total Rac1 and Cdc42 proteins were used in Western blots. Gel bands from Western blot were scanned with LAS, and analyzed using Multi Gauge image analysis software (Fuji Film) (Cho et al, 2007;Kim et al, 2007a).…”
Section: Western Blotting Analysismentioning
confidence: 99%